The Influence of Work Motivation and Work Discipline on Employee Performance Using Promotions at the Special Class I Immigration Office in Surabaya - Budianto Arif (Yayasan Gema Bina Nusantara, 2023)
This study aims to analyze the effect of work motivation and work discipline on employee performance using promotions at the Special Class I Immigration Office in Surabaya. Using quantitative methods and measuring instruments SPSS version 26. Respondents used were 135 respondents. The results of this The Influence of Work Motivation and Work Discipline on Employee Performance Using Promotions at the Special Class I Immigration Office in Surabaya has a significant effect